2010
DOI: 10.1007/s00404-010-1687-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pectopexy: a new technique of prolapse surgery for obese patients

Abstract: This method provides a stable and durable repair. The laparoscopic access reduces morbidity. The operation time for this procedure is approximately 50 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 12 publications
2
85
0
1
Order By: Relevance
“…Biler et al, in the study about abdominal sacropexy, LS and pectopexy, found no occurrences of de novo apical prolapse at 6 months follow‐up. In studies regarding pectopexy, we found one (2.3%) relapse of apical prolapse after pectopexy reported by Noe after 21.8 months of follow‐up and none in the initial study by Banerjee . In the LLS technique group, objective cure rates at the 1‐year follow‐up were 91.6% for the anterior, 93.6% for the apical, and 85.3% for the posterior compartment …”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Biler et al, in the study about abdominal sacropexy, LS and pectopexy, found no occurrences of de novo apical prolapse at 6 months follow‐up. In studies regarding pectopexy, we found one (2.3%) relapse of apical prolapse after pectopexy reported by Noe after 21.8 months of follow‐up and none in the initial study by Banerjee . In the LLS technique group, objective cure rates at the 1‐year follow‐up were 91.6% for the anterior, 93.6% for the apical, and 85.3% for the posterior compartment …”
Section: Resultsmentioning
confidence: 64%
“…In studies regarding pectopexy, we found one (2.3%) relapse of apical prolapse after pectopexy reported by Noe 22 after 21.8 months of follow-up and none in the initial study by Banerjee. 44 In the LLS technique group, objective cure rates at the 1-year follow-up were 91.6% for the anterior, 93.6% for the apical, and 85.3% for the posterior compartment. 25 Biler et al, 28 reported the following procedures concomitantly performed in the pectopexy group (n = 28): 2 anterior and 3 posterior colporrhaphies, and in the LS group (n = 14): 1 anterior and 3 posterior colporrhaphies, 11 culdoplasties and 1 Burch colposuspension.…”
Section: Success Ratementioning
confidence: 84%
See 1 more Smart Citation
“…Recently published studies retrospectively evaluated the outcome of laparoscopic sacropexy in non-geriatric populations [43,44]. In contrast to the vaginal sacrospinous colpopexy, this technique requires the insertion of synthetic mesh materials, which is associated with the risks of mesh erosion or infection and therefore might bear an avoidable complication especially in multimorbid elderly patients [45].…”
Section: Discussionmentioning
confidence: 99%
“…The NPP was developed in 2007, particularly for those cases in which it is difficult to reach the os sacrum. 32 …”
Section: New Methods Of Pectopexy To Correct Pre-existing Descensusmentioning
confidence: 99%